Sustainability Criteria for Homestay Programme - Bee Cheng, Keng; Puad Mat Som, Ahmad; ., . (International Journal of Engineering and Technology, 2018)
This paper aims to understand the role of homestay programme development as a medium for community-based tourism in rural areas. Although many homestay businesses are actively run by the local community, the sustainability of the development is questionable. Attributes from previous research of local communities’ attitude were reviewed and linked to construct a conceptual framework within the scope of homestay tourism. This study is deductive in nature where descriptive analysis is used to generate mean values of the variables. Four variables were tested: financial resources, infrastructure resources, community participation and community empowerment for the mean values. This finding can be used in determining sustainable tourism practice which will be focused on economic, socio cultural and environmental pillars. The descriptive statistical analysis reveals that the community is heavily participating in tourism activities in their village; however, they are not genuinely empowered. Apart from that, financial and infrastructure resources are not in good state and require improvement.